The place of periodicals in literature - Zimmerman, Kate Elizabeth (My University, 1900)
Introduction: During the peaceful reign of Queen Anne in England the social and intellectual activity of the people was quite marked. Coffee houses were established, and when the men met to sip their coffee and smoke, they discussed the topics of the day, criticisms were exchanged along political lines, sensations of the day were noted, as well as the latest productions in literature. This constant companionship made their minds more alert, witty and active to the newest things. One of the direct results of this spread of intelligence is the periodical publications. The Daily Courant was started in 1702. Daniel Defoe began the Review in 1704. But perhaps the first real periodical – part newspaper and part magazine – was the Tatler, in 1709, with Sir Richard Steele and his friend Joseph Addison, as the editors. After two ears, the Tatler was discontinued. In partnership, Addison and Steele edited the Spectator for two years. This paper was succeeded by the Guardian. Addison and Steele wrote as moralists, their methods of reforming the evils of the day are in keeping with the spirit of the times. With delicate tact and unvarying good humor, they made ridiculous the follies of the times. The first real magazine, as we know it now, came out in the beginning of the nineteenth century. In 1802, the first number of the Edinburgh Review appeared, causing a great sensation in the literary circles. The authorship of the articles was kept secret. Jeffry, the editor for thirty years, was an “arch critic”, in fact he set a standard for succeeding periodicals. Thos. Carlyle and Thos. B. Macaulay were contributors to the columns.
Citation: Zimmerman, Kate Elizabeth. The place of periodicals in literature. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Litrerature; Periodicals; Magazines; Theses